2014
DOI: 10.1111/jocn.12506
|View full text |Cite
|
Sign up to set email alerts
|

Swedish nursing students' experience of stress during clinical practice in relation to clinical setting characteristics and the organisation of the clinical education

Abstract: It is important that supervisors are aware that students in hospital departments overcrowded with patients are at risk of stress and may have increased need of support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 33 publications
5
70
0
4
Order By: Relevance
“…To determine the level of stress, the following scaling was used: 2.67-4.00 for high stress, 1.34-2.66 for moderate stress, and 0-1.33 for low stress [26]. The PSS had a Cronbach's alpha coefficient of 0.86-0.89 [2,27] and the content validity index was 0.94 [28]. In the current study, Cronbach's alpha for the total scale was 0.87, indicating adequate internal consistency reliability.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the level of stress, the following scaling was used: 2.67-4.00 for high stress, 1.34-2.66 for moderate stress, and 0-1.33 for low stress [26]. The PSS had a Cronbach's alpha coefficient of 0.86-0.89 [2,27] and the content validity index was 0.94 [28]. In the current study, Cronbach's alpha for the total scale was 0.87, indicating adequate internal consistency reliability.…”
Section: Measurementsmentioning
confidence: 99%
“…Most nursing curricula allocate more than half of the nursing students time for clinical exposure using advanced technical instrumentation and perform nursing skills that may cause severe impairment to their patients, therefore increasing their worry of creating errors. Therefore, they view the clinical area as a very stressful place [2]. Learning challenges of the students in clinical practice may cause stress which may directly or indirectly hinder their performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Å ha to veiledere kunne oppleves som ideelt ved at en fikk et innblikk i ulike måter å gjøre ting på, men det kunne oppleves utfordrende dersom veilederne forventet ulike ting av studentene. Én studie viser at det er en sammenheng mellom opplevelse av stress og antall veiledere (Blomberg, Bisholt, Engström, Ohlsson, Johansson og Gustafsson 2014), spesielt når det forekommer overbelegg av pasienter i avdelingene. I vår studie ble det som opplevdes som utfordrende, beskrevet som travelhet og at veilederne da hadde mindre tid til å følge opp og veilede om nødvendig.…”
Section: å Laere Av Hverandreunclassified
“…Prelab seeks to supplement the didactic course work, helping connect theory and clinical practice. Literature has suggested that prelab improves the student's ability to collect relevant data [7,10,11,12], enhances critical thinking [7,13], strengthens research skills, and promotes self-directed learning [14] Prelab may help students develop a comprehensive plan of care, [7,9,11], anticipate priority nursing diagnoses [10,11,12], identify relevant nursing interventions [10], and implement nursing care plans [10,11,12].…”
Section: Introductionmentioning
confidence: 99%